Strategi Kesantunan dan Ketidaksantunan dalam Tindak Tutur Direktif Guru - Sumarti Sumarti (Universitas Lampung, 2015)
Strategy directive speech acts teachers (STTDG) in learning impact on student affective color. An attempt to